Applying Cultural Project Based Learning to Develop Students’ Academic Writing - Irawati, Lulus (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Writing is considered to be the most demanding and difficult skill for many college students, since there are some steps to be followed such as prewriting, drafting, editing, revising and publishing. The interesting topic like culture including lifestyle, costume, and custom is necessary to be offered in Academic Writing class. Accordingly, this article aims to elaborate the application of a cultural project based learning to develop students’ ability in academic writing. This descriptive qualitative research was conducted in Academic Writing class consisting of 20 students of the fourth semester. The students were divided into some groups, each consisting of 4-5 people assigned to make a cultural project within 6 weeks, in the form of essay. Each member of the groups has to create his/ her own essay and then compile the essays to be a mini-journal. Therefore, one group has one mini-journal consisting of 4-5 essays. To check the content of mini-journal, the lecturer also asked the groups to present in front of the class to get some suggestions, feedback, or comments.